Facing the challenge of hospitality: Ukrainian refugees and local policy in a less developed region - Źróbek-Różańska, Alina; Zysk, Elżbieta; Pawlewicz, Katarzyna; Źróbek-Sokolnik, Anna (Ekonomia i Prawo. Economics and Law, 2024)
Motivation: Since the beginning of the war, Poland has welcomed more than 1.5 million Ukrainian refugees. This new reality has put pressure on local authorities, especially those managing less developed, poorer regions with less experience in receiving immigrants, as they faced the sudden urge to accommodate the needs of these new arrivals. Aim: This article aims to present the profile, needs, and potential of people who have found refuge in less developed areas (i.e., Warmia and Mazury). It helps to anticipate and understand Ukrainian migration — as the influx of refugees has long-term effects, requiring local authorities to take action, i.e., to ensure the availability of social services. Integrating thousands of refugees requires careful planning, developed infrastructure, and funds. It is also worth considering the benefits of the potential of new residents. Another purpose is to share objective knowledge on the effects of the ongoing war. Results: Through the research, it has been possible to obtain a great deal of information about people who found refuge in a less attractive area for migration. Profile of the immigrant was created, and the needs in terms of social infrastructure and the set of advantages that immigrants can offer on the labor market were described.